2009
DOI: 10.1016/s1015-9584(09)60403-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Smoke

Abstract: Surgical smoke is the gaseous by-product formed during surgical procedures. Most surgeons, operating theatre staff and administrators are unaware of its potential health risks. Surgical smoke is produced by various surgical instruments including those used in electrocautery, lasers, ultrasonic scalpels, high speed drills, burrs and saws. The potential risks include carbon monoxide toxicity to the patient undergoing a laparoscopic operation, pulmonary fibrosis induced by non-viable particles, and transmission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 35 publications
0
61
0
4
Order By: Relevance
“…Concerns have been raised regarding the infection risk, mutagenesis and spread of malignant cells. Exposure to surgical smoke is associated with adverse effects on the cardiovascular and respiratory system as well as with increased mortality. Surgical smoke has been demonstrated to have cytotoxic, genotoxic and mutagenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised regarding the infection risk, mutagenesis and spread of malignant cells. Exposure to surgical smoke is associated with adverse effects on the cardiovascular and respiratory system as well as with increased mortality. Surgical smoke has been demonstrated to have cytotoxic, genotoxic and mutagenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The particulate matter consists of chemicals, blood, tissue particles and bacteria. It has been demonstrated that electrosurgical devices may produce high quantities of ultrafine particles (UFP) and fine particles (FP) with diameters mostly in the range from 0.01 μm up to 1 μm [9,10,11]. Larger particle diameters are also produced, and particle peak concentrations are just close to the target tissue [12].…”
Section: Introductionmentioning
confidence: 99%
“…The potential health risks related to the exposures and inhalation of surgical smoke have been linked to acute adverse health effects in exposed healthcare workers [8,9,24,25,26,27], including: eye, nose and throat irritation, headache, cough, and nasal congestion [3,22,28,29]. Surgical smoke has been shown to induce acute and chronic inflammatory changes (e.g., emphysema, asthma, chronic bronchitis) in the respiratory tract of animal models [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long duration exposure to benzene may cause anemia and some other blood disorders. 14,15 Consequently, the surgical smoke poses environmental health risk for both surgeons and the medical staff. 16,17,18 Yet, it has not been proven that it is mutagenic.…”
mentioning
confidence: 99%